A Moraxella catarrhalis vaccine to protect against otitis media and exacerbations of COPD: An update on current progress and challenges - Antonia C. Perez; Timothy F. Murphy (Taylor & Francis Group, 2017)
Moraxella catarrhalis is a major cause of morbidity and mortality worldwide, especially causing otitis media in young children and exacerbations of chronic obstructive pulmonary disease in adults. This pathogen uses several virulence mechanisms to colonize and survive in its host, including adherence and invasion of host cells, formation of polymicrobial biofilms with other bacterial pathogens, and production of β-lactamase. Given the global impact of otitis media and COPD, an effective vaccine to prevent M. catarrhalis infection would have a huge impact on the quality of life in both patient populations by preventing disease, thus reducing morbidity and health care costs. A number of promising vaccine antigens have been identified for M. catarrhalis. The development of improved animal models of M. catarrhalis disease and identification of a correlate of protection are needed to accelerate vaccine development. This review will discuss the current state of M. catarrhalis vaccine development, and the challenges that must be addressed to succeed.